Variedades de batatinhas (Solanum tuberosum L.) procedentes da Holanda: Parte I - Resultados experimentais da primeira plantação, no país, com tubérculos importados em 1947 - Boock,O. J. (1948)
The author reports the results of six experiments with eight yellow fleshed potato varieties from Holland, conducted at six different locations in the State of São Paulo. Time of planting was February-March, less favorable than August-September, because of climatic conditions during the growth period (somewhat dry weather). For this reason, yields were not good. Observations were made on development; resistance, precocity and production of varieties, as well as specific gravety of tubers. Under the conditions of the experiments the varieties Voran and Alpha were the least susceptible to Phytpphthora while Eersteling, and Saskia were the most susceptible. The Doré, Eersteling, Saskia and Geelblon were found to be early maturing varieties while Alpha, Voran and Libertas were late maturing varieties. The varieties Eigenheimer and Bintje revealed themselves the better yielders, with about 7.3 metric tons of tubers per hectare. Yields of next experiments, conducted at September-October, are expected to be better.